Endogeneity in Structural Unemployment Equations : The Case of Canada. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1993)
This paper examines the endogeneity of several structural variables which enter unemployment rate equations-the generosity of unemployment benefits, nonwage labor costs, the relative minimum wage, and the degree of unionization. It finds evidence of reverse causality for these structural variables based on causality tests. The structural unemployment rate equation is then estimated using instruments suggested by the empirical analysis of the structural variables. The paper confirms the earlier finding that the generosity of unemployment benefits, nonwage labor costs, and the relative minimum wage have a significant positive impact on the unemployment rate, but fails to find an effect for the degree of unionization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet